The effect of monitoring and evaluation systems on the performance of selected non-governmental organisations. - Opoku-Agyemang, Perpetua (KNUST, 2025)
Thesis Submitted In Partial Fulfillment Of The Requirements Of The Award Of Executive Masters In Business Administration (Strategic Management And Consulting).